Techno-economic analysis of two-stage anaerobic system for biohydrogen and biomethane production from palm oil mill effluent. Issue 4 (August 2021) - Mahmod, Safa Senan; Jahim, Jamaliah Md; Abdul, Peer Mohamed; Luthfi, Abdullah Amru Indera; Takriff, Mohd Sobri
Abstract: The proliferation of biobased-renewable fuel industries was driven by the depletion of the finite fossil fuel reserves and the rising consciousness on sustainable and environmental consequences. Hence, the present study aims to establish baseline economics for a two-stage anaerobic system by performing a comprehensive analysis using a set of assumptions for what can plausibly be achieved within a twenty-year timeframe. The techno-economic analysis was carried out to elucidate the viability of the proposed anaerobic system that produces biohydrogen (BioH2 ), and biomethane (BioCH4 ) from locally generated palm oil mill effluent (POME). Process modelling and economic analysis were performed using a modelling software SuperPro Designer. The plant conditions were temperature at 50 °C for both stages, and HRT of 1 and 10 days for BioH2 and BioCH4, respectively. The economic profitability assessment demonstrated the feasibility of the project with the dynamic payback period ( DPP ), return on investment ( ROI ), internal rate of return ( IRR ), and net present value ( NPV ) of 8.01 years, 19.87%, 21.48% and USD 4624, 705, respectively. Furthermore, the economics of this system was most sensitive to POME quality and product selling prices. The results revealed that a two-stage anaerobic system might both expand the production of renewable energy and enable improved productivity and revenue of palm oil mills to move forward cleaner production industry. Graphical Abstract: ga1 Highlights: BioH2 and BioCH4 from POME were techno-economically assessed. The system produced 225, 225 m 3 of BioH2 and 51.19 million m 3 of BioCH4 per annum. The production profitability is feasible at payback time (8.01 yr) and IRR (21.48%). The system profitability was most sensitive to POME quality and products selling prices.